Element Accumulation in Mushrooms - Goessler, Walter (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2024)
Mushrooms are important in ecosystems as symbionts, saprotrophs, and parasites. The roles of fungi involve element cycling, rock and mineral transformations, bioweathering, fungal-clay interactions, and metal-fungal interactions. Therefore, fungi can also liberate elements from soil, effectively transform halogens, metals, metalloids, and organometallic compounds by reduction, methylation, and dealkylation. These processes are very important for our ecosystems since transformations of metal(loid)s modify their mobility and toxicity. As it is really difficult to remove soil or rotted wood from the mycelium, fruit bodies are mainly investigated for the transformed elements from soil. Moreover, fruit bodies serve as important nutrient source for parasites, wild animals, and also humans. It is not commonly known that fruit bodies may accumulate remarkable concentrations of (trace) elements. The well-known King Bolete (Boletus edulis) is known to accumulate the essential trace element selenium but on the other hand this fungus also accumulates significant amounts of mercury. The Fly Agaric (Amanita muscaria) is a selective vanadium accumulator. Several hundreds of mg V/kg dry mass have been determined. Thelephora penicillata was found to be a cadmium accumulating mushroom (more than 1000 mg Cd/kg). The Violet Crown Cup (Sarcosphaera coronaria), a mushroom considered edible in previous days, has been reported as an arsenic accumulator with close to 1% of arsenic on a dry mass basis. The edible Ink Stain Bolete (Cyanoboletus pulverulentus) is also capable of accumulating up to 1300 mg As/kg. The False Chanterelle (Hygrophoropsis aurantiaca) was discovered to be an iron accumulating mushroom with up to 5000 mg Fe/kg. The presentation covers analytical aspects as well as results for total element determinations and elemental speciation in different mushroom species.